Awareness, Preparedness, and Practices of Hospital Staff During COVID-19 Pandemic in Saudi Arabia: Lessons Learned - Abdulrahman Alanazi; Mukhtar Ansari; Gehad M. Subaiea (Journal of Pharmacy and Bioallied Sciences)
Background and Objective: Healthcare professionals working in hospitals face an especially high risk of contracting and spreading the 2019-nCoV virus. Given this elevated risk, evaluating their awareness and preparedness is critical before managing the rising cases of 2019-nCoV infections. Materials and Methods: This cross-sectional study was conducted in different regions of Saudi Arabia from July to September 2020. A total of 269 healthcare workers participated, including doctors, nurses, pharmacists, and other professionals involved in COVID-19 care. Participants were recruited through convenience sampling for an online survey. The survey, structured based on the CDC checklist and a prior Zika outbreak survey, was disseminated via Google Forms in response to the urgent and highly contagious nature of the pandemic. Data analysis was conducted using IBM SPSS Statistics 21.0, applying one-way analysis of variance and Pearson Chi-square tests to examine relationships between demographic factors and key outcomes. Results: Of the 269 respondents, around two-thirds (65.1%, n = 175) were women. Nearly half were employed at public tertiary care hospitals. Levels of awareness, preparedness, and practices among staff in handling the COVID-19 outbreak ranged from 88% to 93%, 68% to 88%, and 74% to 86%, respectively. Interestingly, the staff’s awareness, preparedness, and practices were significantly influenced (P < 0.05) by their specialty and the type of healthcare facility. Conclusion: Although the hospital staff showed adequate awareness about COVID-19, there is still considerable room for improvement in their preparedness and practices. To better manage the pandemic and ensure both safety and quality of life for healthcare workers, coordinated strategies and continuous follow-up efforts are crucial.